2012
DOI: 10.1627/jpi.55.219
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Formation from Biomass Model Compounds and Real Biomass by Partial Oxidation in High Temperature High Pressure Water

Abstract: However, the yield of hydrogen was lower than expected and further improvement of the two-step reaction process is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It has been revealed that hydrolysis of cellulose, which is main component of carbohydrate in biomass, is rapid in sub and supercritical water without additive [34,35]. The hydrolysis product of cellulose, glucose, is converted into furan ring compounds [8][9][10][11][12][13] and further small molecules (including hydrogen gas) in hydrothermal and supercritical water in the presence and absence of catalyst/additive [34,[36][37][38][39][40][41][42][43].…”
Section: Carbohydrate Conversion Into Precursors Of Liquid Fuelsmentioning
confidence: 99%
“…It has been revealed that hydrolysis of cellulose, which is main component of carbohydrate in biomass, is rapid in sub and supercritical water without additive [34,35]. The hydrolysis product of cellulose, glucose, is converted into furan ring compounds [8][9][10][11][12][13] and further small molecules (including hydrogen gas) in hydrothermal and supercritical water in the presence and absence of catalyst/additive [34,[36][37][38][39][40][41][42][43].…”
Section: Carbohydrate Conversion Into Precursors Of Liquid Fuelsmentioning
confidence: 99%
“…The leakage of microwave was monitored by a microwave survey meter (Holiday Industries Inc., Model HI-1501) for safety and found to be less than 1 mW/cm 2 at distance of 5 cm far away from the microwave oven. The temperature inside the reactor is monitored and controlled by the control box (16). The temperature and power of microwave were monitored and recorded using a computer (21).…”
Section: Concept For Development Of a New Microwave Heating Apparatusmentioning
confidence: 99%
“…At first, fructose conversions into 5-hydroxylmethyl furfural (HMF), which is an important chemical block, in the presence of catalysts at hydrothermal condition [14] or in water mixture [15] are introduced. Second, we described partial oxidation of glycerol into formic acid with hydrogen peroxide at hydrothermal condition [16] . Both the hydrothermal reactions are described in the next section.…”
Section: Topics Described In This Chaptermentioning
confidence: 99%
See 2 more Smart Citations